Improving a Multimodal Based Teacher Training Program for Teachers of Gifted: An Educational Design Research - Gul, Muhammet Davut; Costu, Bayram (FAC TEACHER EDUCATION, 2024)
This study is an educational design research on the design, implementation, and evaluation of a Multimodal Based Teacher Training Program (MB-TTP) that aims to improve the representational competence skills of teachers of gifted (ToG). The aim was to describe the design process of the model and the development process of ToG during and after the intervention. Participants were chosen by convenience sampling. The data were collected through the multimodal representations designed by the teachers, their comments on these representations, discussions on the designs and models in the classrooms, and interviews with participants and experts. The data obtained from the artifacts were analyzed according to the analytical framework developed by the researcher. Interviews and discussions were analyzed through content analysis. At the end of micro cycle 1 and 2, the findings showed that teachers gained abilities of identifying, but they were not qualified at selecting/ designing and evaluating. At the end of micro cycle 3 and 4, the findings revealed that teachers were able to identify different types of intermodal mechanisms, and their design purposes. At the end of micro cycle 5, the results showed that teachers were able to identify and analyze the adequacy of multimodal representations, as well as to critique the extent to which the representation reflected the relationships between the modes indicated. Finally, the MB-TTP and its design principles were revealed as the result of all these iterations. The findings showed that applying the MB-TTP and its principles improve representational competence skills of ToG.
Keywords: educational design research; gifted education; multimodality; teacher training; representational competence; REPRESENTATION; MULTIPLE; STUDENTS; COMPETENCE; STRATEGIES; MOTIVATION; CLASSROOM; KNOWLEDGE; THINKING; MODEL; Education & Educational Research